2016
DOI: 10.1007/s12665-016-6195-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term forest cover changes, within an agricultural region, in relation to environmental variables, Lubelskie province, Eastern Poland

Abstract: Land cover changes result mainly from anthropogenic determinants (historical and socio-economic processes), but natural factors may also play an important role. The processes of deforestation and reforestation are important elements of present-day landscape changes in Central Europe. In this study, the relation of forest cover changes to environmental variables (topography and soils) within an important agricultural region of Poland, the Lubelskie province (25,000 km 2 ), over the last 180 years was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Poland has a long-standing tradition of tobacco cultivation and is one of its largest producers in the European Union 36. What is specific to tobacco cultivation is its high labor intensity, low level of mechanization and significant amount of manual work, which leads to a significant exposure to biological aerosols 26,37,38. Another factor increasing the concentration of bacteria and mold fungi in the air in the Lubelskie voivodeship may not be anthropogenic bioaerosol exclusively from farming but also naturally occurring from forests, parks and meadows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poland has a long-standing tradition of tobacco cultivation and is one of its largest producers in the European Union 36. What is specific to tobacco cultivation is its high labor intensity, low level of mechanization and significant amount of manual work, which leads to a significant exposure to biological aerosols 26,37,38. Another factor increasing the concentration of bacteria and mold fungi in the air in the Lubelskie voivodeship may not be anthropogenic bioaerosol exclusively from farming but also naturally occurring from forests, parks and meadows.…”
Section: Discussionmentioning
confidence: 99%
“…Forests in the Lubelskie voivodeship show considerable diversity in terms of distribution and size of forest complexes and most of all in terms of habitats and phytosociology. According to official statistics by Zgłobicki, forests cover only 23% of the area (the average for Poland: 30%)26 (Figure 1).
Figure 1A map showing the Pomeranian and Lubelskie voivodeships in Poland.
…”
Section: Selection Of Sampling Sitesmentioning
confidence: 99%
“…The results did not show a role for soil properties or population density as drivers of forest cover in the eighteenth century. An effect of soil properties on forest cover was shown for the Central European lowlands [36,42,43], where more fertile soils were usually deforested. Similarly, Ciupa et al [70] found a higher deforestation rate on soil suitable for agriculture in the Świętokrzyskie Mts, however this was not tested statistically.…”
Section: Local Drivers Of Changes In Forest Covermentioning
confidence: 99%
“…Nowadays, GIS techniques allow us to quantitatively analyze historical data [33]. In Poland, access to historical maps is limited [34], and therefore the usefulness of such historical maps in ecological studies is rather restricted [21,[35][36][37]. The historical analysis has concentrated mostly on the Carpathian region [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that heavy metals stored in street dust not only pollute the soil and air of urban areas but also accumulate in alluvia and constitute a threat for the hydrosphere. They are washed away during rainfall events and accumulate in water sediments in the Bystrzyca river valley, downstream of the city (Zgłobicki et al 2016a, b). Street dust may be considered as one of the main factors of such pollution.…”
Section: Discussionmentioning
confidence: 99%